A Critical Review of Legal Protection Against E-Money Users in Indonesia - Saivol Virdaus; Nasrulloh Ali Munif (Universitas Muhammadiyah Sidoarjo, 2019)
Protection of e-money users must be done based on the increasingly advanced science and technology. The formulation of the problems in this study are: (1) What is the legal provision regarding e-money as a means of payment in commercial transactions in Indonesia? (2) What is the legal protection of e-money users in conducting commercial transactions in Indonesia? The formulation of the problem was studied in depth using the normative juridical approach. The results of this study are: First, e-money is regulated in Bank Indonesia Regulation Number 10/8 / PBI / 2008 concerning Amendments to Bank Indonesia Regulation Number 7/52 / PBI / 2008 concerning the implementation of Card-Based Payment Instrument Activities. Bank Indonesia Regulation Number 16/8 / PBI / 2014 concerning Amendments to Bank Indonesia Regulation Number 11/12 / PBI / 2009 concerning Electronic Money (Electronic Money). E-money issuers as regulated in Article 1 paragraph (1) of Bank Indonesia Regulation Number 16/8 / PBI / 2014 are Banks and Non-Bank Institutions incorporated in the form of Limited Liability Companies (PT). While the legal status / relationship between the holders of electronic money with the issuer of e-money money is based on the contract of sale and purchase, which has been regulated in Article 1457 of the Civil Code. Second, legal protection for e-money users can be done in two ways, namely: Preventive Legal Protection and Repressive Legal Protection